Study on Self Compacting Concrete using Industrial Waste Material (Steel Slag) - B. Lakshmi, Vinay Kumar Merugu, Vyas A, Krishna Solanki, Malika Katukam (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This work aims to study the possibility of recycling floor steel slag as fine aggregate in the manufacturing of self-compacting concrete (SCC). For this; the sand is substituted with floor steel slag at different percentages (0, 5, 10, 15, 20 and 25). The slump flow diameter and T50, as well as compressive and split tensile strength in hardened state of the different SCC mixes, are determined, analyzed and compared with control concrete. The obtained results show that some physical and mechanical characteristics of SCC mixes with floor steel slag are better than those of conventional Self-compacting concrete. This study, as well, insures that reusing floor steel slag in SCC gives a positive approach to reduce the cost of materials and solve some environmental problems.